FTIR-ATR Monitoring and SEC/RI/MALLS characterization of ATRP synthesized hyperbranched polyacrylates - Gonçalves, Miguel A.D. (2009)
This work reports the synthesis at 1 L scale of hyperbranched polyacrylates based upon acrylate/diacrylate monomers such as n-butyl acrylate (nBA)/1,6-hexanediol diacrylate (HDDA) and using atom transfer radical polymerization (ATRP). A FTIR-ATR immersion probe was used to monitor the polymerization reaction.